2016
DOI: 10.1016/j.prnil.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of age, prostate-specific antigen, and prostate volume in Indonesian men with benign prostatic hyperplasia

Abstract: BackgroundTo investigate the relationship between age, prostate specific antigen (PSA), and prostate volume (PV) in Indonesian men with histologically proven benign prostatic hyperplasia.MethodsData were generated from our BPH database from June 1994 until December 2013. Subjects were men with a minimum age of 40 years with chief complaint of LUTS or urinary retention, diagnosed with BPH. All patients underwent TRUS-guided prostate biopsy. Patients with PSA level >10 ng/mL were excluded from the study to exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…The current evidence trends towards the level of both total and free PSA being directly proportional to PV [28][29][30][31]. This study confirms this relationship as our data showed a direct correlation between the level of PSA and PV (r = 0.247, p = 0001).…”
Section: Discussionsupporting
confidence: 84%
“…The current evidence trends towards the level of both total and free PSA being directly proportional to PV [28][29][30][31]. This study confirms this relationship as our data showed a direct correlation between the level of PSA and PV (r = 0.247, p = 0001).…”
Section: Discussionsupporting
confidence: 84%
“…Sebagai gambaran terdapat 1040 kasus dalam kurun waktu 3 tahun (1994-1997) di dua rumah sakit di kota Jakarta. 15 Di Indonesia, Putra et al 16 menemukan adanya korelasi antara kadar PSA dan volum prostat di kota Jakarta. Selain genetik, perbedaan pola hidup dan status ekonomi dapat menjadi faktor yang berpengaruh terhadap insidensi BPH.…”
Section: Pendahuluanunclassified
“…PSA is prostate specific but not specific to prostate cancer. 4,5 The increased value of PSA is found in 20% to 50% of men with BPH. 4 Approximately 10% of the male population has a PSA value higher than 10 ng/ml but do not have cancer.…”
Section: Introductionmentioning
confidence: 99%